Peran Humas Dalam Membentuk Citra Pemerintah - Evawani Elysa Lubis (JIANA ( Jurnal Ilmu Administrasi Negara ), 2012)
This study aims to find outand considers the role of Public Relations of the Secretariat of Riau Province in Shaping a positiveimage of the Provincial Government of Riau. In additions, to investigate the factors inhibiting andsupporting activities of the Secretariat of Public Relations Riau Province in shaping a positive imageand the media used. The method used is descriptive qualitative data from informants collected andprocessed in qualitative way. The results showed that the role of Riau Provincial Relations Secretariatbase on Regional Regulation No. 2 Tahun 2005 has not been implemented optimally for the task inrunning the affairs and public relations activities more through mass media. Inhibiting factors RiauProvincial Secretariat of Public Relations in the formation of positive image of the Government ofRiau Province, among others, human resources, political factors, the structure of governmentorganizations in Riau Province, inadequate infrastructure to support public relations activities, andlack of coordination between the Regional Secretariat of Public Relations in Riau Province andpublic relations who exist in the Provincial Government of Riau. Factors supporting public relationsactivity Riau Provincial Secretariat received direct funding from the budget of Riau Province,motivation to improve the quality and quantity of human resources.